Studying a Possible Placebo Effect of an Imaginary Low-Calorie Diet - Panayotov, Valentin Stefanov (Frontiers in Psychiatry, 2019)
In recent years the prevalence of obesity in developed countries has increased to the point that some authorities have coined the term “obesity epidemics”. Combining energy intake control measures (via diet) with protocols for increasing energy expenditure (predominantly via low to medium intensity aerobic exercise) proved to be the most effective approach in addressing this problem. In this experiment, we studied for a possible placebo effect of a weight loss program on changes in body mass and fat tissue in overweight or obese people. 14 healthy adults of both sexes aged between 19 and 45 with Body Mass Index (BMI) > 27 participated in the study. They were randomly assigned to 2 groups – one experimental and one control. The subjects in the experimental group followed an isocaloric diet but were told they were put on a calorie-deficient regimen. The subjects in the control group were aware they followed an energy-balanced diet. All participants were engaged in regular sessions of resistance exercise 3 times a week with the total energy cost of approx. 750-900 kcal/week. We studied within-group differences in body mass, percentage of fat tissue and BMI. All 3 variables reduced in value in the experimental group: body mass – 9.25 ± 5.26 kg, percentage of fat tissue – 3.4 ± 0.97% and BMI – 2.88 ± 1.50. Despite some methodological biases of the study construct, in our opinion, the changes of the parameters in the experimental group could be explained by a placebo effect of the intervention.